THE DENGUE VACCINES: ASSESSMENT OF FUTURE PROSPECTS, TREATMENT, AND VACCINE CHALLENGES - KALYANI, GADE; N, THANUSHREE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: As per the national survey data, the prevalence of dengue has been still rising consistently, and the burden of the disease is predominantly affecting the adults with progression toward the DF, dengue hemorrhagic fever, and dengue shock syndrome. The higher hospitalization rate result in massive mortality. Methods: Vector control alone cannot reduce the transmission of viral infection, so effective vaccine development is made high priority. Results: Several vaccine candidates including live attenuated, live chimeric, inactivated and many other vector vaccines are key elements needed to achieve the dengue public health targets. Global strategies like diagnosis, care management, outbreak preparedness and integrated surveillance, sustainable vector control, and future vaccine implementation are needed to be addressed. Conclusion: This review mainly describes the dengue treatment challenges, in addition to a brief discussion of dengue vaccine challenges and future outlook on dengue that might help in making efficacious vaccine in near future.